2022
DOI: 10.3390/epigenomes6030016
|View full text |Cite
|
Sign up to set email alerts
|

Global m6A RNA Methylation in SARS-CoV-2 Positive Nasopharyngeal Samples in a Mexican Population: A First Approximation Study

Abstract: The Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) is the causal agent of COVID-19 (Coronavirus Disease-19). Both mutation and/or recombination events in the SARS-CoV-2 genome have resulted in variants that differ in transmissibility and severity. Furthermore, RNA methylation of the N6 position of adenosine (m6A) is known to be altered in cells infected with SARS-CoV-2. However, it is not known whether this epitranscriptomic modification differs across individuals dependent on the presence of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Fourth, the m 6 a modification pathway is hijacked by several RNA viruses (e.g., influenza A, HCV, HBV, EV71, HIV) for propagation and persistence [98][99][100][101] and, accordingly, sites of m 6 A modification are conserved in various SARS-CoV-2 variants 80 , highlighting a potential evolutionary function of these sites in transmission and epidemiology. Indeed, Batista-Roche et al reported that SARS-CoV-2 variants (epsilon > B.1.1.519 > alpha/gamma > omicron) and vaccination status (unvaccinated > partially-vaccinated > vaccinated) modulated genome and/or viral m 6 A levels differentially 102 . Taken together, our data suggest that methyltransferase inhibitors (G9a/Ezh2) can be repurposed into broad-spectrum antivirals and represent a novel class of host mechanism-directed therapeutics to counter emerging drug resistance and infection.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the m 6 a modification pathway is hijacked by several RNA viruses (e.g., influenza A, HCV, HBV, EV71, HIV) for propagation and persistence [98][99][100][101] and, accordingly, sites of m 6 A modification are conserved in various SARS-CoV-2 variants 80 , highlighting a potential evolutionary function of these sites in transmission and epidemiology. Indeed, Batista-Roche et al reported that SARS-CoV-2 variants (epsilon > B.1.1.519 > alpha/gamma > omicron) and vaccination status (unvaccinated > partially-vaccinated > vaccinated) modulated genome and/or viral m 6 A levels differentially 102 . Taken together, our data suggest that methyltransferase inhibitors (G9a/Ezh2) can be repurposed into broad-spectrum antivirals and represent a novel class of host mechanism-directed therapeutics to counter emerging drug resistance and infection.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that vaccinated individuals showed significantly lower m6A methylation levels than unvaccinated individuals (n = 8 and 52, respectively), and that differences in m6A methylation levels across variants in unvaccinated individuals were significant; however, no significant correlation was observed between m6A methylation levels and viral load (nucleocapsid gene expression) or age [36]. According to the study, a complete vaccination scheme denoted the administration of one or two doses (depending on the vaccine specifications) of authorized vaccines in Mexico, including AZD1222, CoronaVac, BNT162b2, Ad5-nCOV, and mRNA-1273, developed by AstraZeneca, Sinovac, Pfizer-BioNTech, CanSinoBio, and Moderna, respectively.…”
Section: Alterations In M6a Methylation Induced By Mrna Vaccinesmentioning
confidence: 92%
“…In a study carried out by De Jesus et al [35], m6A RNA sequencing in human T2DM islets revealed several hypomethylated transcripts involved in insulin secretion; in addition, the depletion of m6A methylation levels in beta cells induced cell cycle arrest, decreased beta cell proliferation, and impaired insulin degranulation and secretion. We previously reported that m6A levels were significantly lower in individuals infected with SARS-CoV-2 variants delta and omicron compared to other variants and uninfected individuals [36]; however, the possible alterations to m6A RNA methylation levels by SARS-CoV-2 variants in beta cells have not been reported yet, even though RNA methylation is a potential key player in understanding and treating COVID-19 [37].…”
Section: Molecular Mechanisms Involved In Nodac Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Jorge Luis Batista-Roche et al report that the level of global m6A RNA methylation differs in COVID-19 patients’ samples infected by SARS-CoV-2 variants. For example, m6A levels were significantly lower in the variants of concern (VOC) delta- and omicron-positive individuals compared to non-infected individuals and individuals with complete vaccination schemes showed significantly lower m6A levels than unvaccinated individuals [ 1 ]. One of the reviews (Beatriz Martinez-Delgado et al) [ 2 ] discusses epigenomic approaches for the diagnosis of rare diseases that are based on functional aspects of the genome, including studies that have successfully provided diagnoses for complex undiagnosed cases.…”
mentioning
confidence: 99%